First Language and Second Language in the Multilingual Context - Voudina Ngarsou (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2022)
Studies in English continues to gain ground in different countries and from different perspectives to the extent that some concepts need to be rethought. For this reason, the first language (L1) and second language (L2) in a multilingual setting were examined. This study was motivated by the fact that despite the extensive research into language teaching and language learning, little was clear about L1 and L2 in the context where many indigenous languages coexist with European languages and others. As example, Chad which is a multilingual country has French and Arabic as official languages, and English is given the status of a foreign language. Many studies in English in non-native English speaking environment considered the students’ mother tongue as L1, but the current research aimed to show that the first language could refer to the second language and rethink what are called first language and second language in research on English language learning by contextualising the situation. Qualitative method was used. It did not involve the collection of data. It was based on literature: books, articles, and opinions. So, from the body of the paper, the findings showed that many studies in English referred to the first language not as the speaker’s mother tongue, but the second language. This meant that L1 in terms of the students’ native languages (indigenous languages) should not be included in studies that involve the influence of L1 on English, unless the L1 that refers to the native language is made clear in the study.